ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR SISWA DALAM MATA PELAJARAN PPKn di SMA 05 PONTIANAK - Ramadayanti, Sisi; Utomo, Bambang Budi; Purnama, Shilmy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to find out, describe, and analyze the factors of student learning difficulties in PPKn SMAN 05 Pontianak subjects. This research uses descriptive method with the typoo of research is descriptive research. The research instrument is the researcher himself. Sources of data for school principals, PPKn subjects, and students of class X IPS 2 of SMAN 05 Pontianak. Data collection techniques in this study are direct observation technique, interview, and documentation. Data collection procedures based on the presence of researchers using the five senses and perceptions. Data analysis technique is a qualitative approach, and while the data validity testing technique is using triangulation techniques, sources, and time. The study found that the description/conditions of student learning difficulties in class X IPS 2, namely: learning disorder, learning disabilities, learning disabilities, underachievement, and slow learning. Internal factors of student learning difficulties, namely: health, intelligence, feelings and self-confidence, motivation and interests, individual differences, and the ability to remember. Then the external factors of student learning difficulties inculude: teachers who pay less attention to students, inadequate learning facilities, lack of attention from parents, and friends who get along which leads to negative directions.and the efforts made by the teacher provide remedial, use varied methods and provide motivation. It can be concluded that many students who have difficulty learning PPKn in class X IPS 2.Keywords: Learning Difficulties, Civic Education, SMA Negeri 05 Pontianak.